REGISTER AND POWER IN INDONESIAN ONLINE GAME (A SOSIOLINGUISTIC STUDIES) - Rayditya Brillian Prima (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2019)
The use of language variations in online games are determined by several factors such as time, place, and situation that results in the emergence of the practice of power. This arises because the production of text is strongly influenced by the context in which in a game, there is a need to win the game. The purposes of this paper is to reveal the forms of registers and their applications that shape the practices of power within them. Data obtained from observations in the game. The data were then analyzed using a sociolinguistic approach by using a semiotic triangle of Halliday as the blade of analysis. The results of this paper indicate that the use of registers focuses on interaction among team and another team members in mocking each other. The conclusion of this paper is that the player who has the best ability, has the authority to manage other gamer's games and can mock his opponent team members as well as his own team.